EDUKASI CUCI TANGAN PAKAI SABUN DAN SIKAT GIGI PADA ANAK USIA SEKOLAH DI SD N 129/1 SIMPANG RANTAU GEDANG - Hidayati, Fajrina; Wisudariani, Evy; Hubaybah, Hubaybah; Butar Butar, Marta; Rahmat, Andree Aulia; Putri, Fitria Eka (Jurnal Salam Sehat Masyarakat (JSSM), 2024)
A large number of children, 30% of the total population of Indonesia or around 73 million people, and school age is a golden period to instill the values of clean and healthy living behavior (PHBS) so that they have the potential to become agents of change to promote PHBS, both in the school environment, family and community. The first step in carrying out this activity is preparation. At this stage what is done is to prepare an activity plan and then all the infrastructure needed. At the implementation stage, what was done was coordinated with the principal and teachers of SDN 129 on September 11, 2023, to ask permission to conduct counseling activities on hand washing with soap and how to brush teeth properly at SDN 129. The implementation of educational activities in the form of counseling on hand washing with soap and tooth brushing at SDN 129/1 Simpang Rantau Gedang Village showed positive results, the students were enthusiastic about participating in the activity and there was an increase in their knowledge about how to wash their hands with soap and brush their teeth properly and correctly, where students could answer quiz questions asked during the quiz session.